(untitled) (Revista Contexto & Educação, 2026)
This article aims to stimulate critical and systematic reflection on the reality regarding the importance of higher education institutions, which, through dialogue and action, develop and promote educational policies to combat violence against women in academia. It problematizes the importance of combating violence against women in academia and discusses the relevant social role of higher education institutions in preventing, confronting, and containing potential violence against women in higher education. The method used combines dialectics with the meta-epistemology of contexts, considering the possibility of producing the study descriptively with a mixed approach. The results indicate that the government, in collaboration with academic institutions, has promoted public policies to combat violence against women. However, the promotion of public policies must be consistent and efficient, so that, in the social reality, they are effective in curbing and preventing any type of violence against women in university settings. Our perspective is to propose critical reflections on the topic, collaborating to stimulate a culture through action in reality, of non-violence in society and in university spaces through scientific knowledge with the intention of promoting social awareness against any type of violence in academic spaces, especially against women or against any person, since academia must be a space of well-being and social security.